Penerapan Logika Fuzzy Metode Sugeno Untuk Optimalisasi Nilai Ekspor Ikan Tuna Hs 160414 Ke Italia - Luthfia Rohimah; Sinta Rukiastiandari; Juarni Siregar (Universitas Bina Sarana Informatika, 2020)
To fund the ongoing development at this time the State requires income from various sources such as income from exports. Export is an activity of sending goods abroad where the activity will produce value. And Indonesia's export value which is quite high comes from non-oil and gas exports, one of which is the export of processed tuna 160414. One of the destination countries for the export of processed tuna which is quite high is Italy. The purpose of this study is to find out the best method for predicting the value of processed tuna exports to Italy in the application of fuzzy logic in order to optimize the value of exports. The results showed that the Sugeno method is a good method. The Sugeno method has results that are quite close to the actual results with an error rate of 41%, so the Sugeno method can be used as a recommended method in predicting the optimal amount of Indonesia's 160414 HS exports to Italy.